Epidemiological survey on the oral health of cattle slaughtered in Goiás, Brazil - Caetano, Geovanna Domingues da Cunha; Martins, Andressa da Silva; Cardoso, Maria Vitória Soares; Paula, Warley Vieira de Freitas; Saraiva, Júlia Rebecca; Borges, Naida Cristina; Schweitzer, Christiane Marie [UNESP]; Júnior, Elerson [UNESP]; Dutra, Iveraldo dos Santos [UNESP]; Borsanelli, Ana Carolina (Wiley, 2025)
Background: Good oral health is essential for the performance and welfare of cattle, as it directly affects their feed intake and feed efficiency. However, little is currently known about the epidemiology of dental disease in cattle. Methods: This study investigated the prevalence of lesions in the dental arcades of 1006 slaughtered cattle. The periodontal evaluation was performed by the same person, using a periodontal probe and flashlight as the heads passed down the slaughter line, and the results were recorded on an odontogram. Results: Of the 1006 slaughtered animals evaluated, 115 (11.4%) were male and 891 (88.6%) were female; 735 (73.1%) were beef cattle and 271 (26.9%) were dairy cattle. Gingival recession was more frequent in incisors, while periodontal pockets were observed mainly in incisors and molars. Dairy cattle showed a higher prevalence of gingival recession and periodontal pockets than beef cattle. In beef cattle, an association was observed between age and gingival recession, while in dairy cattle, age was linked to tooth wear. No significant differences were observed between males and females. Limitations: As the examinations were carried out postmortem, it was not possible to evaluate the prevalence of gingivitis. Conclusion: The findings of this study contribute to our understanding of the complex relationship between sex, breed type, age and oral health in cattle, highlighting the need for further research to clarify these associations and develop targeted management strategies to promote animal health and welfare.
Keywords: cattle; epidemiology; periodontitis; tooth wear